Evaluation of a yeast β-glucan blend in a pet food application to determine its impact on stool quality, apparent nutrient digestibility, and intestinal health when fed to dogs - Kilburn-Kappeler, Logan R.; Aldrich, Charles G. (Frontiers in Animal Science, 2023)
Oral supplementation of β-glucans may be able to improve the health of companion animals. However, little is understood regarding the effects of yeast β-glucan on diet processing and intestinal function. Therefore, the objectives of this research were to determine the carry through of yeast β-glucan during extruded diet production and its impact on diet utilization by dogs. Three diets were formulated to contain increasing levels of a yeast β-glucan blend at 0, 0.012 and 0.023% inclusion. Processing inputs were held constant during extrusion to allow for evaluation of output parameters and physical characteristics of kibble. Yeast β-glucan concentration was analyzed in extruded diets using the glucan enzymatic method, resulting in >100% recovery. Twenty-four Labrador Retrievers were assigned to one of three dietary groups of 8 dogs each with an equal distribution of sex and age. Dogs were fed dietary treatments for 24-d adaption followed by 4-d total fecal collection. Feces were scored on a 1-5 scale, with 1 representing liquid diarrhea and 5 hard pellet-like with a fecal score of 3.5-4 considered ideal. Fresh fecal samples were collected for analysis of short chain fatty acid concentrations. Apparent total tract digestibility was calculated by total fecal collection (TFC) and titanium (TI) marker methods. Data were analyzed using a mixed model procedure in software (version 9.4, SAS Institute, Inc., Cary, NC). Dry bulk density, kibble diameter, and kibble length did not differ among dietary treatments. Intake was similar among dietary treatments (P > 0.05). Dogs required about 26% more food than estimated [130*BWkg0.75] to maintain body weight among all treatments. Fecal score was not different (P > 0.05) among dietary treatments but was lower than ideal at an average of 2.6. Nutrient digestibility was not affected (P > 0.05) by inclusion of the yeast β-glucan. By method, the TFC procedure resulted in higher (P < 0.05) digestibility values when compared to the TI procedure. In addition, yeast β-glucan did not alter short or branched chain fatty acid proportions. Overall, processing parameters, physical characteristics of kibble, stool quality, nutrient digestibility, and intestinal health in dogs were not affected by the yeast β-glucan blend.